2021
DOI: 10.1097/ogx.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in First Trimester Pregnancy: A Cohort Study

Abstract: (Abstracted from Hum Reprod 2021;36(1):40–47) Pregnant women are at an increased risk of viral infections and increased risk of serious morbidity such as severe pneumonia, particularly during the first trimester. COVID-19 (coronavirus disease 2019) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Miscarriages: Four studies [ 19 , 27 , 37 , 43 ] contained information on miscarriages and were included in the analysis. The risk of miscarriage was unexpectedly reduced in patients compared with controls (OR 0.564; CI 95% 0.364; 0.875; p = 0.0) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscarriages: Four studies [ 19 , 27 , 37 , 43 ] contained information on miscarriages and were included in the analysis. The risk of miscarriage was unexpectedly reduced in patients compared with controls (OR 0.564; CI 95% 0.364; 0.875; p = 0.0) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the risk for miscarriage in patients and controls. Crovetto et al, 2021 [ 19 ]; Wang et al, 2021 [ 8 ]; Bortoletto et al, 2021 [ 27 ]; la Cour Freiesleben et al, 2021 [ 37 ]. …”
Section: Figurementioning
confidence: 99%
“…Moreover, the hypothesis of SARS-CoV-2 infection changing the endometrial gene expression profile of its associated receptors and proteases leading to alteration of the endometrial receptivity status remain under question. Despite of the many issues unresolved to date, clinical data reported no increasing risk of pregnancy loss for patients with SARS-CoV-2 infection during the first pregnancy trimester compared to non-infected patients [26], suggesting no impact of SARS-CoV-2 on the endometrial receptivity status and successful implantation.…”
Section: Discussionmentioning
confidence: 95%
“…The available data, on the other hand, show that SARS-Cov-2 infection is not associated with an increased risk of early pregnancy loss and are in line with our results: an Italian case-control study showed no significant difference in the cumulative incidence of COVID-19 in women who experienced spontaneous abortion than in those with ongoing pregnancy ( 13 ). A Danish cohort study found no significantly increased risk of early pregnancy loss in women with SARS-Cov-2 infection and demonstrated that women in their first trimester have not an increased risk of severe COVID-19 disease ( 14 ). A Canadian study showed that the outbreak does not seem to affect early first-trimester miscarriage rates in asymptomatic patients ( 15 ).…”
Section: Discussionmentioning
confidence: 99%